RUTI Vaccination Enhances Inhibition of Mycobacterial Growth ex vivo and Induces a Shift of Monocyte Phenotype in Mice - Prabowo, Satria A.; Painter, Hannah; Zelmer, Andrea; Smith, Steven G.; Seifert, Karin; Amat, Merce; Cardona, Pere-Joan; Fletcher, Helen A. (Frontiers in Immunology, 2019)
Tuberculosis (TB) is a major global health problem and there is a dire need for an improved treatment. A strategy to combine vaccination with drug treatment, termed therapeutic vaccination, is expected to provide benefit in shortening treatment duration and augmenting treatment success rate. RUTI candidate vaccine has been specifically developed as a therapeutic vaccine for TB. The vaccine is shown to reduce bacillary load when administered after chemotherapy in murine and guinea pig models, and is also immunogenic when given to healthy adults and individuals with latent TB. In the absence of a validated correlate of vaccine-induced protection for TB vaccine testing, mycobacterial growth inhibition assay (MGIA) has been developed as a comprehensive tool to evaluate vaccine potency ex vivo. In this study, we investigated the potential of RUTI vaccine to control mycobacterial growth ex vivo and demonstrated the capacity of MGIA to aid the identification of essential immune mechanism. We found an association between the peak response of vaccine-induced growth inhibition and a shift in monocyte phenotype following RUTI vaccination in healthy mice. The vaccination significantly increased the frequency of non-classical Ly6C- monocytes in the spleen after two doses of RUTI. Furthermore, mRNA expressions of Ly6C--related transcripts (Nr4a1, Itgax, Pparg, Bcl2) were upregulated at the peak vaccine response. This is the first time the impact of RUTI has been assessed on monocyte phenotype. Given that non-classical Ly6C- monocytes are considered to play an anti-inflammatory role, our findings in conjunction with previous studies have demonstrated that RUTI could induce a balanced immune response, promoting an effective cell-mediated response whilst at the same time limiting excessive inflammation. On the other hand, the impact of RUTI on non-classical monocytes could also reflect its impact on trained innate immunity which warrants further investigation. In summary, we have demonstrated a novel mechanism of action of the RUTI vaccine, which suggests the importance of a balanced M1/M2 monocyte function in controlling mycobacterial infection. The MGIA could be used as a screening tool for therapeutic TB vaccine candidates and may aid the development of therapeutic vaccination regimens for TB in the near future.